2020
DOI: 10.1002/jts.22563
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Trauma Exposure: Count Versus Variety of Potentially Traumatic Events in a Binational Sample

Abstract: Traumatic event checklists typically ask respondents to indicate whether they have experienced particular types of potentially traumatic events (PTEs) and then sum these endorsements to gauge cumulative trauma exposure. However, the sum of these endorsements indicates the variety of PTEs respondents have experienced rather than the count of exposure events. The main objective of the present study was to explore the association between PTE count and variety to examine assumptions regarding the use of traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Another limitation is that the extent of trauma exposure was measured by summing the different types of events that adolescents reported, which will underestimate the number of actual events experienced for young people who experienced more than one exposure to the same type of event. A recent large, cross-national (US–Mexico) trauma study demonstrated that while the number of trauma event types typically correlates very highly with actual event counts, this association is reduced at extremely high levels of trauma exposure (Rasmussen et al, 2020 ). Nonetheless, in the same study, the different types of trauma experienced were a stronger predictor of PTSD than the overall quantity of events.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the extent of trauma exposure was measured by summing the different types of events that adolescents reported, which will underestimate the number of actual events experienced for young people who experienced more than one exposure to the same type of event. A recent large, cross-national (US–Mexico) trauma study demonstrated that while the number of trauma event types typically correlates very highly with actual event counts, this association is reduced at extremely high levels of trauma exposure (Rasmussen et al, 2020 ). Nonetheless, in the same study, the different types of trauma experienced were a stronger predictor of PTSD than the overall quantity of events.…”
Section: Discussionmentioning
confidence: 99%
“…Cecil et al, 2017 ; Vacek & Whisman, 2020 ), or (3) a count (summed) score to represent multiple CT exposure (e.g. Cloitre et al, 2009 ; Rasmussen et al, 2020 ). These approaches are considered ‘variable-centred’, where the focus is on trauma exposure (Houston et al, 2011 ; Shevlin & Elklit, 2008 ), whereas latent class analysis (LCA) shifts the level of analysis to the individual and has been supported as the optimal method to model trauma exposure patterns (O’Donnell et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, as the SLESQ is a conventional traumatic event type checklist, it should be kept in mind that the total number of PTEs is not quantified by counting the occurred traumatic events per se, retrospectively recalled by the adolescents. Nevertheless, it is likely that particularly in refugee pre-migration contexts, there are risks for (a) a higher number of potentially traumatic events as well as (b) a greater variety of these events, thus leading to a strong correlation between the count and variety [ 45 ]. Especially for adolescents who have survived war and other traumatic events, the variety score appeared to have strong predictive power with respect to mental health outcomes [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially for adolescents who have survived war and other traumatic events, the variety score appeared to have strong predictive power with respect to mental health outcomes [ 13 ]. Moreover, the variety score might even be a stronger predictor when directly compared to the count, based on the possibility that a habituation effect could occur with certain—but not all—repetitive types of traumatic events (e.g., viewing corpses in war zones), attenuating the association with mental health [ 45 ]. Further, experiencing a higher variety of traumatic events can trigger a multitude of problems that need to be overcome simultaneously, which might lead to a range of deteriorated mental health outcomes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%